Differences in decreasing of swimming pace in elite swimmers in the 100 meter backstroke discipline - Trboljevac, I.; Mijalkovic, S.; Ðurovic, M. (Journal of Anthropology of Sport and Physical Education, 2023)
The aim of this research was to determine the differences in swimming pace between the finalists and semifinalists of the 2019 World Championships in the discipline of 100 m backstroke held in the South Korean city of Kwangju in 2019. The research was carried out on 16 swimmers (8 finalists and 8 semi-finalists), using 8 variables for evaluating swimming pace. Differences between groups were determined using the Student`s T-test of independent samples. No statistically significant differences in swimming pace were found between the finalists and semi-finalists of the World Championships, but there was a statistically significant difference in passing times in favor of the finalists. The finalists were faster in the first and second passing times than the semi-finalists, while their pace drop is numerically smaller compared to the semi-finalists, but not statistically significant.